An Analysis of Escapism in Tennessee Williams’ “The Glass Menagerie” - natalina, Sry; Rotua Elfrida2 (The Explora, 2023)
This study deals with Tennessee Williams’ work, The Glass Menagerie based on psychological analysis. The characters in the play are intentionally made to identify the attitudes and behaviors of each character in order to give up clear descripion of the characters. In the Glass Menagerie there are three characters who try to escape from reality but they have different psychological problem in life. Living in illusion is Amanda’s way to escape, playing the glass figure is the way of Laura to escape from reality, while the way of Tom to escape is going to the movies. The purpose of analyzing the literary work is to display clearly about the psychological element in the play and also moral lesson clearly. Keywords: Escapism, psychological, The portrait of Tennessee Williams